A Comparative Analysis of the Role of Audit Partners in Preventing Material Misstatements Arising from Fraud in Financial Statements: A Grounded Theory Study in Iran and Iraq - Sabah khudhair, Anwar; Doaei, Meysam; Abed Mousa Alsabary, Ibrahim; Alimoradi, Mohammad (Business, Marketing, and Finance Open, 2026)
The purpose of this article is to provide a comparative analysis of the role of audit partners in preventing material misstatements arising from fraud in financial statements, with a specific focus on Iran and Iraq. Adopting a qualitative approach and employing the grounded theory methodology, this study seeks to address an existing gap in the literature through in-depth semi-structured interviews with experienced audit partners in Iran and Iraq. The findings indicate that audit partners in both countries face a set of common challenges—albeit with differing intensity and manifestations. The most significant factors undermining their independence and effectiveness include: (1) managerial pressures and occupational threats, (2) financial dependence and concentration within the audit market, (3) weaknesses in regulatory and legal oversight structures, (4) shortages of technological infrastructure and auditing tools, and (5) the lack of effective inter-organizational communication and continuous professional training. In Iran, the supervisory system exhibits relatively greater coherence but is influenced by institutional and economic relationships; whereas in Iraq, severe infrastructural deficiencies, political instability, and the absence of independent oversight bodies substantially amplify both the scope and intensity of these threats. The conceptual model derived from data analysis identifies six principal threats to the independence and performance quality of audit partners. In addition to the five classical threats recognized in the IFAC/IESBA framework, the model introduces “technological threat” as an emerging dimension in environments characterized by low levels of digital maturity. The results demonstrate that without reforming oversight structures, investing in advanced auditing technologies, and strengthening a professional culture grounded in independence, the role of audit partners in preventing fraud-related misstatements will be seriously constrained. The innovation of this study lies in its focus on gaps in the existing literature and in developing, for the first time, a localized model of threats and influencing mechanisms affecting audit partner performance in two countries with differing institutional and technological contexts. This model can serve as a foundation for designing policies aimed at enhancing audit quality and reducing the risk of financial fraud at the regional level.